ABC adherence and impact of optimal medical therapy in heart failure patients with atrial fibrillation. (3rd October 2022) - Bonini, N; Proietti, M; Romiti, G F; Vitolo, M; Fawzy, A M; Ding, W Y; Fauchier, L; Marin, F; Nabauer, M; Potpara, T S; Dan, G A; Boriani, G A; et al.
Abstract: Background: Heart failure (HF) has close association with atrial fibrillation (AF). The ESC guideline recommended Atrial fibrillation Better care (ABC) pathway aims to reduce major cardiovascular adverse outcomes with an integrated care approach. Optimal medical treatment (OMT) represents the cornerstone in HF management. Purpose: To investigate the variables affecting OMT treatment and its impact, in conjunction with ABC pathway adherence (vs non-adherence, ie.no ABC), in a large contemporary cohort of European AF patients with HF enrolled in the ESC-EHRA EORP-AF General Long-Term Registry. Methods: OMT was defined as treatment with Angiotensin-converting-enzyme inhibitors (ACE-i)/ Angiotensin receptor blockers (ARBs) with Beta-Blockers and/or Mineralocorticoid receptor antagonists (MRAs), and compared to non-OMT adherence ("no OMT"). A logistic regression analysis explored factors associated with OMT adherence. We identified three patient groups: (i) HF with no OMT/no ABC; (ii) HF with OMT/no ABC; (iii) HF with OMT/ABC. Primary outcome was a composite outcome of all-cause death and major adverse cardiac events (MACE). Results: Among the original 11096 patients enrolled, 9857 (88.8%) were included in this analysis. Among these, 3819 (38.7%) had HF. Compared to non HF patients, those with HF were older, more likely female, had more comorbidities and higher thromboembolic risk. OMT prevalence was 2228/3819 (58.3%), while ABC adherence was 23.3%. On logistic multivariable regression, increasing age, higher BMI and higher frailty index were associated with OMT adherence, while male sex, anemia, renal disease and EHRA II–IV were inversely associated with OMT adherence. According to three HF groups, the rates of composite outcome progressively decreased (HF with no OMT/no ABC 26.4%; HF with OMT/no ABC 24%, HF with OMT/ABC 19%; p<0.001). Kaplan Meier curve showed progressively lower cumulative risk for the composite outcome across the three groups with the lowest risk among HF patients with OMT/ABC (Log-rank: p=0.002) [Figure 1]. Adjusted Cox regression analysis showed that when compared to HF with no OMT/no ABC group, there was a progressively lower risk with OMT and/or ABC adherence (HF with OMT/no ABC: HR 0.81 [95% CI, 0.64–1.02]; HF with OMT/ABC: HR 0.68 [95% CI, 0.5–0.92]). Conclusions: After two years of follow-up, in a large contemporary cohort of European AF patients with HF, OMT adherence was suboptimal, being influenced by several clinical factors, determining a low adherence to the ABC pathway. OMT alone showed a non-significant reduction in composite outcome events. Conversely HF patients managed with OMT in the context of ABC pathway adherence showed the best reduction in risk of adverse outcomes. Funding Acknowledgement: Type of funding sources: Other. Main funding source(s): Since the start of EORP, the following companies have supported the programme: Abbott Vascular Int. (2011–2021), Amgen Cardiovascular (2009–2018), AstraZeneca (2014–2021), Bayer (2009–2018), Boehringer Ingelheim (2009–2019), Boston Scientific (2009–2012), The Bristol Myers Squibb and Pfizer Alliance (2011–2016), The Alliance Daiichi Sankyo Europe GmbH and Eli Lilly and Company (2011–2017), Edwards (2016–2019), Gedeon Richter Plc. (2014–2017), Menarini Int. Op. (2009–2012), MSD-Merck & Co. (2011–2014), Novartis Pharma AG (2014–2020), ResMed (2014–2016), Sanofi (2009–2011), SERVIER (2010–2021), and Vifor (2019–2022). - I agree that this information can be anonymised and then used for statistical purposes only